Inducing cellular senescence in vitro by using genetically encoded photosensitizers - Petrova, Nadezhda V. (Aging (Albany NY), 2016)
Cellular senescence, a form of cell cycle arrest, is one of the cellular responses to different types of exogenous and endogenous damage. The senescence phenotype can be induced in vitro by oncogene overexpression and/or DNA damage. Recently, we have reported a novel mechanism of cellular senescence induction by mild genotoxic stress. Specifically, we have shown that the formation of a small number of DNA lesions in normal and cancer cells during S phase leads to cellular senescence-like arrest within the same cell cycle. Here, based on this mechanism, we suggest an approach to remotely induce premature senescence in human cell cultures using short-term light irradiation. We used the genetically encoded photosensitizers, tandem KillerRed and miniSOG, targeted to chromatin by fusion to core histone H2B to induce moderate levels of DNA damage by light in S phase cells. We showed that the cells that express the H2B-fused photosensitizers acquire a senescence phenotype upon illumination with the appropriate light source. Furthermore, we demonstrated that both chromatin-targeted tandem KillerRed (produces O(2)(−)) and miniSOG (produces (1)O(2)) induce single-stranded DNA breaks upon light illumination. Interestingly, miniSOG was also able to induce double-stranded DNA breaks.